A minimally invasive bipolar surgical approach for the treatment of patellar fracture using the tension-band wiring technique - Lin, Zhangxiong; Chen, Yaoqing; Wang, Hai; Lan, Wenbin; Xie, Yun; Wu, Gui (Frontiers in Surgery, 2022)
Objective Minimally invasive surgical techniques are becoming increasingly popular for the treatment of traumatic injuries. Although some minimally invasive techniques in the management of patellar fractures have been reported, the limited exposure in such methods may cause technical difficulties during surgery and restrict their wide application. In this context, this study aims to introduce a bipolar incision and assess the clinical outcomes of patellar fractures treated via this type of incision. Materials and methods Patients who suffered patellar fractures and who received surgical treatment via bipolar incision between 2018 and 2020 in our hospital were retrospectively reviewed and included in this study. The clinical and radiological records of all patients were reviewed. A classification of the fractures was done and intraoperative parameters, Visual Analog Scale (VAS) score, knee range of motion, and the Hospital for Special Surgery (HSS) knee score of the patients were evaluated and summarized. Results The study included 19 patients who met the inclusion criteria. All patellar fractures were operated through the minimally invasive bipolar surgical approach. The mean time of operation was 69.0 ± 8.5 min. The mean time to union was 12.8 ± 2.1 weeks. The average total knee range of motion was 131.8 ± 4.4°, and the average HSS score was 97.1 ± 2.6 at 1-year post-operation. No surgical-related complications were observed. Conclusions The knee functional outcomes were favorable when patellar fractures were treated through the minimally invasive bipolar incision method. This bipolar surgical approach was found to be a feasible method for treating patellar fractures.